![image](https://tex.z-dn.net/?f=3%5E%7B2x%2B1%7D%2B8%5Ccdot+3%5E%7Bx%7D-3%3D0%5C%5C%5C%5C3%5Ccdot3%5E%7B2x%7D%2B8%5Ccdot+3%5E%7Bx%7D-3%3D0%5C%5C%5C%5Ct%3D3%5Ex%3E0%5C%5C%5C%5C3t%5E2%2B8t-3%3D0%5C%5C%5C%5CD%3D100%5C%5C%5C%5Ct_1%3D+%5Cfrac%7B-8%2B10%7D%7B6%7D+%3D+%5Cfrac%7B1%7D%7B3%7D+%2C%5Cquad+t_2%3D+%5Cfrac%7B-8-10%7D%7B6%7D+%3C0%5C%5C%5C%5C+%5C%5C+%5Cfrac%7B1%7D%7B3%7D%3D3%5Ex+%5C%5C+%5C%5Cx%3D-1)
0\\\\3t^2+8t-3=0\\\\D=100\\\\t_1= \frac{-8+10}{6} = \frac{1}{3} ,\quad t_2= \frac{-8-10}{6} <0\\\\ \\ \frac{1}{3}=3^x \\ \\x=-1" alt="3^{2x+1}+8\cdot 3^{x}-3=0\\\\3\cdot3^{2x}+8\cdot 3^{x}-3=0\\\\t=3^x>0\\\\3t^2+8t-3=0\\\\D=100\\\\t_1= \frac{-8+10}{6} = \frac{1}{3} ,\quad t_2= \frac{-8-10}{6} <0\\\\ \\ \frac{1}{3}=3^x \\ \\x=-1" align="absmiddle" class="latex-formula">